A VALUE-DRIVEN YOUTH DEVELOPMENT FRAMEWORK FOR KEMENPORA: INTEGRATING GOVERNANCE, KPIS, AND MULTI-STAKEHOLDER COLLABORATION - Mira Dallima Andini; DR Manahan Parlindungan Saragih Siallagian (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
Youth development is part of Indonesia's long-term strategy to create better human capital and can help realize the vision of Indonesia Emas 2045. With its responsibility for youth affairs, Kemenpora has an essential role to play in increasing the quality of Indonesian youth; improving their levels of participation; and developing their character and contributions. Kemenpora currently has a number of foundations to build youth development, such as policy directions for youth development, youth development programs, regulatory support, networks with stakeholders, and the Youth Development Index or Indeks Pembangunan Pemuda (IPP), which are used at a macro level to measure youth development. The problem is not the lack of foundations, but the low degree of integration between values, programs, governance, measurements, and collaboration with stakeholders. The objective of this research is to develop a new youth development framework for Kemenpora by employing a values-driven approach. Specifically, the values are Patriotism, Grit, and Empathy. A qualitative and design-oriented case study methodology is employed. Data collection is carried out using document analysis and semi-structured expert interviews with three key experts from Kemenpora. Analysis employs the Resource-Based View (RBV); VRIO model; PESTEL; SWOT/TOWS models; and thematic analysis to determine what the internal resources/capabilities of Kemenpora are; what are the external factors influencing Kemenpora; where are there strategic gaps; and what are some outputs from the framework? Findings indicate that Kemenpora has many good aspects as institutions (i.e., national mandate, regulatory authority, existing programs, stakeholder networks, etc.) however, there is a significant gap in integrating strategic values with program design; governance mechanisms with program level KPIs; stakeholder collaboration with implementing programs; and implementing readiness with all prior factors. Thematic analysis produces five practical outputs: a Value-to-Program Alignment Matrix, Governance Roles and Responsibilities Model, KPI-Based Monitoring & Evaluation Framework, Multi-Stakeholder Collaboration Cycle, and Phased Implementation Roadmap. These outputs provide the foundation for a proposed new youth development framework for Kemenpora. This article provides both theoretical knowledge on how to manage public sectors and operational knowledge on how to implement youth development practices through providing a structured framework that enables practitioners to take strategic youth values and convert them into program designs; governance roles/responsibilities; measurable indicators; stakeholder collaborations; and phased implementations. In addition, the proposed framework will be complementary to the use of IPP and facilitate a transition from activity-based program delivery to value-driven; outcomes-focused; measured; governed; and collaborative youth development management.